Wild tembelek plant (Lantana camara) as a potential bioactive natural product againts Streptococcus pyogenes in Indonesia - Ricky Indra Alfaray; Rafiqy Sa'adiy Faizun; Lionardy Yodianto; Saruuljavkhlan Batsaikhan; Yudith Annisa Ayu Rezkitha (Universitas Muhammadiyah Surabaya, 2020)
Abstract Infectious diseases are common problems in most countries. Streptococcus pyogenes is the infectious agent that causes diseases such as pharyngitis, impetigo, toxic shock syndrome, and necrotizing fasciitis. Tembelek (Lantana camara) is a wild plant that can easily be found in every ecosystem in Indonesia whether in nature or settlements and known as a plant that has an antibacterial effect but the knowledge about its potential against Streptococcus pyogenes in this past five years remain scant. The aim of this study was to determine the potentiality of Lantana camara leaves and flowers extract against Streptococcus pyogenes. In this experimental study, in vitro using Post-test Only Control Group Designed, has been done and confirmed by the Indonesian Institute of Sciences. Lantana camara leaves and flowers extracts were obtained by maceration using ethanol. The extracts were diluted into eight concentrations and their antibacterial activity against Streptococcus pyogenes was tested using the Kirby-Bauer disc then proceeded Minimum Inhibitory Concentration (MIC) test and phytochemical assay. The data processed using SPSS software version 22. The results showed that flowers extract had the most significant inhibition zone (11.85 ± 0.119 mm) compared with the leaves extract (9.54 ± 0.07 mm) at the highest tested concentration was 640 mg/ml. The MIC of both extracts was 250 mg/ml. Flavonoids, phenolic, steroids, and saponins were found in both extracts whereas, alkaloid was found only in flowers extract. In conclusion, the Tembelek plant has an antibacterial effect against Streptococcus pyogenes. Future study is needed related to its mechanism of antibacterial effect. Keywords : Antibacterial potential, Lantana camara; Streptococcus pyogenes